2000
DOI: 10.1109/42.870265
|View full text |Cite
|
Sign up to set email alerts
|

Unmatched projector/backprojector pairs in an iterative reconstruction algorithm

Abstract: Computational burden is a major concern when an iterative algorithm is used to reconstruct a three-dimensional (3-D) image with attenuation, detector response, and scatter corrections. Most of the computation time is spent executing the projector and backprojector of an iterative algorithm. Usually, the projector and the backprojector are transposed operators of each other. The projector should model the imaging geometry and physics as accurately as possible. Some researchers have used backprojectors that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(165 citation statements)
references
References 11 publications
5
160
0
Order By: Relevance
“…The effect of including positron blurring in both forward and backward projection operations is investigated in [23], where it is shown that the use of positron blurring during backprojection has a smoothing effect on the reconstructed image leading to a delayed convergence, requiring a large number of iterations to reach a comparable detail level. Furthermore in [24] it is shown that MLEM algorithms demonstrate first a short convergent trend but then deviates from the desired solution, independent from the projector/backprojector pair matching. The authors concluded that the concrete choice for the backprojector may not be a very critical factor in a practical image reconstruction problem.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of including positron blurring in both forward and backward projection operations is investigated in [23], where it is shown that the use of positron blurring during backprojection has a smoothing effect on the reconstructed image leading to a delayed convergence, requiring a large number of iterations to reach a comparable detail level. Furthermore in [24] it is shown that MLEM algorithms demonstrate first a short convergent trend but then deviates from the desired solution, independent from the projector/backprojector pair matching. The authors concluded that the concrete choice for the backprojector may not be a very critical factor in a practical image reconstruction problem.…”
Section: Discussionmentioning
confidence: 99%
“…(4) and (5). However, it was shown that an unmatched forward and backprojector can even improve convergence rates of reconstruction algorithms [19,37].…”
Section: Listing 2 Optomo Operatormentioning
confidence: 99%
“…Indeed, positron range blurring is only taken into account in the projection operation. This approach has been used in several works [14,15] where it is shown that good reconstructed images can be attained with full modeling of blurring effects during the projection step, whereas a simplified modeling is employed into the backprojector.…”
Section: Positron Range Simulationsmentioning
confidence: 99%